Prevalence of common soil-transmitted roundworm infections among residents, aged 4-12, of the Islamic Center, Quiapo, Manila - Abu-Alhayja, Khalid (Animo Repository, 1994)
Fecal samples were collected from 288 children residents, aged 4-12 years of Barangay Islamic Center, Quiapo, Manila. Formalin-ether concentration technic was used to prepare the specimen for detection of the eggs of Ascaris lumbricoides, Trichuris trichiura and hookworms. Ascariasis had an overall prevalence rate of 30.21 percent while trichuriasis and hookworm infection had 15.63 percent and 6.6 percent prevalence rate, respectively. Ascaris infections were noted to be highest among the respondents belonging to the 4-6 age group. Trichuriasis and hookworm infections were both found to be highest among the respondents belonging to the 7-9 age group.Mixed infection with ascariasis and trichuriasis was found in 3.47 percent of the respondents, while 2.08 percent of the respondents had mixed infection with Trichuris and hookworm. The prevalence rates of ascariasis and trichuriasis of 28.4 percent and 12.8 percent, respectively among males were noted to be higher compared to the female group where the infection rates were 25.7 percent and 8.6 percent for ascariasis and trichuriasis, respectively. However, statistical analysis showed that the difference between the prevalence rates of ascariasis in males and females was not significant, while for trichuriasis it was found to be significantly different. The prevalence rate of 5.6 percent for hookworm infection in the female group was higher than that of 2.8 percent in the male group. This difference was found to be highly significant. The intensity of ascariasis was found to be of a very light degree in both sexes for all age groups. Trichuriasis was found to be of a heavy degree among males aged 4-6 years and moderate in the other male and female age groups. Mean egg counts of hookworms in all of the male age groups showed a moderate degree of infection, while those belonging to the 4-6 age group of the females was found to have a very light infection. The other age groups among the female respondents showed a light degree of infection. The study showed that the low body weight of the respondents could not be correlated with the presence of the parasitic infections.